TINGKAT KESUKAAN BAKSO IKAN BERBAHAN BAKU DAGING IKAN PELAGIS KECIL - Junianto, Junianto; Aufa, Indrawan; Banafsaj, Khansa; Zakira, Hanna (Universitas Teuku Umar, 2024)
One of the most abundant fish resources in Indonesian waters. Almost all small pelagic fish caught landed in Indonesia are consumed locally because the price is relatively cheap and tastes good, so it is thought that their contribution to meeting the community's need for protein from fish is very real (Fauziah 2010). In Indonesia, there are various methods of processing fish, one of which is making fish balls. The aim of this research was to determine the level of preference for fish meatball products for small pelagic fish meat types. The method used was experimental research with treatment of 3 types of small pelagic fish meat, namely flying fish, mackerel and trevally. The parameters observed are the level of preference based on organoleptic characteristics which include appearance, aroma, texture and taste. The analysis used is Friedman analysis followed by a multiple comparison test if there are differences between treatments. The best decision making is done using the Bayes method. From the research results, it can be concluded that the fish meatballs with the three treatments were not significantly different.